Penerapan Metode Six Sigma Terhadap Distribusi Barang Healthcare untuk Meminimalisir Terjadinya Keterlambatan Pengiriman PT. Rajawali Nusindo Cabang Jakarta 2 Tahun 2021 - Anastasia, Sinta; Ferdiansyah, Anton; Poncotoyo, Wahyu (Institut Transportasi dan Logistik Trisakti, 2023)
PT. Rajawali Nusindo Jakarta Branch 2 is a company in the distribution of healthcare such as medical devices, vaccines, medicines and consumer goods with intense competition, and has a target in the delivery of one day service to prove to customers that it can meet customer needs. and provide the best quality service. The purpose of writing this thesis is to find out in depth about the problems that cause delays in the delivery of healthcare goods. The research method used by Six Sigma and assisted by DMAIC analysis tools is expected to be able to carry out an improvement and improvement consistently on the problems studied. The results of the research obtained are that there are several problem factors that cause delays in the delivery of healthcare goods, namely over delivery or work, staff who are less focused, high demand at certain times, system errors sometimes, weather, late getting information on warehouse stock updates, lack of transportation fleets, an error occurred in the arrival of goods from the factory, and the customer did not fill in the complete requirements.